Corporate Governance and Financial Markets: A Case of Nepalese Commercial Banks - Pathak, Srijana; Karki, Manisha Kumari; Pant, Kaushiki; Gyawali, Safal; Rawat, Ramesh (Nepalese Journal of Business, 2025)
The study examines the corporate governance and financial markets in the context of Nepalese commercial banks. Return on assets and return on equity are selected as the dependent variables. The selected independent variables are board size, board independence, audit committee, institutional ownership, female director, and number of meetings. The study is based on secondary data of 10 commercial banks with 110 observations for the period from 2012/13 to 2022/23. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of corporate governance and financial markets in the context of Nepalese commercial banks. The study showed that board size has a positive impact on return on equity and return on assets. It indicates that higher the board size, higher would be the return on equity and return on assets. Similarly, board independence has a positive impact on return on equity and return on assets. It indicates that increase in board independence leads to increase in return on equity and return on assets. In contrast, audit committee has a negative impact on return on equity and return on assets. It indicates that increase in audit committee members leads to decrease in return on equity and return on assets. Likewise, number of meetings has a negative impact on return on equity and return on assets. It indicates that higher the number of meetings, lower would be the return on equity and return on assets. However, female directors have positive impact on return on equity and return on assets. It indicates that increase in female directors in the board leads to increase in return on equity and return on assets. In addition, institutional ownership has a positive impact on return on equity and return on assets. It indicates that higher the number of shares held by the entities, higher would be the return on equity and return on assets.